Braver : a wombat's tale - Selfors, Suzanne; Ranson, Walker (Imprint : Square Fish, 2022)
Lola Budge is a wombat who lives with her family in the Northern Forest, and she wants nothing more than something exciting to happen. After she discovers an exiled predator who kidnaps the peaceful wombats including her parents, Lola embarks on an adventure to save her family. She sets off to meet with the Queen of Tassie Island, and Lola will need all the bravery and courage she can muster to survive the journey.